Spring 1999 field reports, Ann Johnson - Johnson, Annet al (1999)
An annotated list of birds sighted by Ann Johnson. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1999. Epson - sheet feed